COVID-19 and public health risk communication in Manipur: a phone-based cross-sectional study - Kayina, T. Kayia Priscilla; Rajkumari, Bishwalata; Keisam, Avinash; Chelladurai, Chelsia; Touthang, Jangkholun; Rajkumari, Joshna; Samurailatpam, Priyanka; Devi, Ningthoujam Suchitra (International Journal Of Community Medicine And Public Health, 2020)
Background: In the fight against COVID-19, communication remains as one of its most important strategic tools. To facilitate healthy behaviour among the general public, Central and State governments has been carrying out various awareness generating activities. This study plans to assess the adequacy of these activities by investigating people’s response by assessing their knowledge, attitudes and actions. Methods: This cross sectional study was conducted among 1493 adults (≥ 18years) residents of Manipur state selected through Random Number Dialling of mobile numbers using a pre-tested interview schedule. Descriptive statistics were generated and multiple logistic regression analysis was performed to test for association. A p-value of <0.05 was taken as significant. Approval was obtained from the institutional ethics committee. Results: The average age of the participants was 34.3 years with females constituting 51%. Majority were aware of the common symptoms i.e. Fever (94.5%), Cough (87.1%), Difficulty in breathing (74.9%) of COVID-19. Preventive measures of hand-hygiene, wearing masks and social distancing were known to 90.3%, 94.8% and 75.6% respectively. Almost 60% agree that the lockdown imposed has worsened their daily living, and more than four-fifth of the participants were stressed and worried. Increase in level of education and per capita income per month was significantly associated with the higher knowledge regarding COVID-19 (p<0.05). There was gap in knowledge and practice and wrong practices were seen. Conclusions: A change in the health communication messages with emphasis on the need for correct practices through appropriate channels and community engagement is urgently required at this hour.